2008
DOI: 10.1038/sj.ki.5002706
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of anionic sites in the glomerular basement membrane by heparanase does not lead to proteinuria

Abstract: Heparan sulfate in the glomerular basement membrane has been considered crucial for charge-selective filtration. In many proteinuric diseases, increased glomerular expression of heparanase is associated with decreased heparan sulfate. Here, we used mice overexpressing heparanase and evaluated the expression of different heparan sulfate domains in the kidney and other tissues measured with anti-heparan sulfate antibodies. Glycosaminoglycan-associated anionic sites were visualized by the cationic dye cupromeroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 46 publications
(66 reference statements)
3
36
0
Order By: Relevance
“…In support of this notion, pretreatment of normal human kidney sections with the active recombinant human heparanase did not reduce the presence of unmodified heparan sulphate (detected by anti-K5 mAb), whereas a complete loss or significant reduction of modified heparan sulphate domains (detected with antibodies JM403 and EW3D10 or HS4C3 respectively) was seen. Consistent with these studies, we have also found that only the unmodified heparan sulphate domain can be detected by the anti-K5 antibody in the GBM of transgenic mice overexpressing heparanase [27]. Taken together, our observations strongly suggest that agrin gene expression and biosynthesis of the heparan sulphate precursor are not reduced in human diabetic nephropathy and that the reduction of modified heparan sulphate domains with N-unsubstituted glucosamine residues and sulphated heparan sulphate domains is due to accelerated degradation by increased heparanase production.…”
Section: Discussionsupporting
confidence: 88%
“…In support of this notion, pretreatment of normal human kidney sections with the active recombinant human heparanase did not reduce the presence of unmodified heparan sulphate (detected by anti-K5 mAb), whereas a complete loss or significant reduction of modified heparan sulphate domains (detected with antibodies JM403 and EW3D10 or HS4C3 respectively) was seen. Consistent with these studies, we have also found that only the unmodified heparan sulphate domain can be detected by the anti-K5 antibody in the GBM of transgenic mice overexpressing heparanase [27]. Taken together, our observations strongly suggest that agrin gene expression and biosynthesis of the heparan sulphate precursor are not reduced in human diabetic nephropathy and that the reduction of modified heparan sulphate domains with N-unsubstituted glucosamine residues and sulphated heparan sulphate domains is due to accelerated degradation by increased heparanase production.…”
Section: Discussionsupporting
confidence: 88%
“…The concentration of heparanase in the glomeruli was significantly increased at all time points in the course of the disease; it is thus probable that heparanase expression is augmented in the early stages of the disease (Kramer et al 2006). The addition of aldosteron to cultured podocytes results in increased heparanase mRNA and protein expression, which is inhibited by spironolactone (van den Hoven et al 2009). …”
Section: Other Diseasesmentioning
confidence: 99%
“…1 The permselectivity of this barrier has been considered to reside principally in the GBM and in the podocyte slit diaphragm, whereas fenestrated endothelial cells and the endothelial cell surface layer (ESL) have attracted lesser attention. Nevertheless, the classical view of the GBM as a major contributor to the permselectivity of the glomerular barrier has been challenged, [2][3][4][5] and a decade of extensive research regarding the podocytes has given important information about numerous proteins of the slit diaphragm that can cause proteinuria when defective. [6][7][8] Simultaneously, experimental evidence has accumulated for the presence of a permselective cell surface layer covering the luminal face of glomerular endothelial cells.…”
mentioning
confidence: 99%